Big Data: Deriving Business Value byleveraging Customer Intelligence - Dhar, Jagrati; Agnihotri, Nishant (International Journal of Computer Sciences and Engineering, 2025)
Businesses are approaching times where ‘Customer Experience’ and ‘Customer Experience Management’ (CEM) are taking the center stage for planning of marketing and business strategies. When we talk of big data Analytics helping to improve Business Intelligence, it all comes down to Customer Intelligence. Not only how to improve services andproducts, but how to provide customized services for customers. Customer-centric organizations and businesses have a definite advantage over their counterparts who are investing in traditional product-centric values. There is an increasing consensus among the business communities that using and relying on big data analytics is going to be an indispensable and integral part of developing Business Intelligence. Big data Analytics are helping businesses with millions of customers to identify individual customer needs by bringing unstructured data into fold. This paper is aimed to examinethe facet of how Big Data Analytics is being used to gain better insights into Customer Intelligence and helping organizations make better Business decisionsto gain competitive advantage.